Politeness and Speech Acts of Malay Kupang - Vera Riyanti Menno (LPPM UNY, 2015)
The study was aimed at examining the use of polite language (language use) in Kupang Malay speech community. There are two basic theories of this research; speech act and linguistic politeness theory. The politeness theory was combined with speech act theory, because the speech act theory investigates what to choose, while the theory of politeness investigate whether the utterances are polite or not. In speech, the BMK speaker also uses the six the principles of politeness toward the listeners. These principles are tact maxim, generosity maxim, approbation maxim, modesty maxim, agreement maxim, and sympathy maxim